Frequency estimation of flow induced vibration in thin cantilever plate - Javeed, Abdulhakeem; Kafafy, Raed; Idres, Moumen; Ihsan, Sany Izan (2013)
This paper presents a model for design and analysis of thin cantilever plate for flutter based micro generators. The analytical model formulates the flow induced response on the cantilever plates at various parameters and determines the frequency of flutter which is crucial in designing and selecting proper geometry for a flutter based micro generator. The model makes use of a novel method to solve flutter frequency by equating two different formulations of lift and moment force induced in the structure during the flow. The frequency analysis conducted in this study shows that the thin cantilever plate’s flutter frequency reduces with increase in its width and varies minimal to change in length.